2018
DOI: 10.4236/ojneph.2018.84010
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury during Malaria in Togolese Children

Abstract: Objective: To describe clinical, biological and evolutionary profile of Acute Kidney Injury (AKI) due to Severe Malaria in the pediatric department. Methodology: This was a retrospective descriptive study that took place from January to December 2012. It has been included children aged 0-15 years admitted for severe malaria with positive thick drop. AKI was defined by using the modified RIFLE (Risk Injury Failure Loss End stage) classification for Pediatrics. Results: 338 children admitted for severe malaria w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Children aged less than 5 years were 1.8 times more likely to develop AKI compared to those aged 5 years and more (Table 2). Similarly Oshoma et al [17] in Nigeria found that the [6] in Uganda found a median age of 3.2 years. This can be explained by the fact that children less than 2 years were shown having a high risk of developing AKI in high transmission area of malaria [6].…”
Section: Factors Associated With Aki Among Children With Severementioning
confidence: 86%
See 2 more Smart Citations
“…Children aged less than 5 years were 1.8 times more likely to develop AKI compared to those aged 5 years and more (Table 2). Similarly Oshoma et al [17] in Nigeria found that the [6] in Uganda found a median age of 3.2 years. This can be explained by the fact that children less than 2 years were shown having a high risk of developing AKI in high transmission area of malaria [6].…”
Section: Factors Associated With Aki Among Children With Severementioning
confidence: 86%
“…Children aged less than 5 years were 1.8 times more likely to develop AKI compared to those aged 5 years and more ( Table 2 ). Similarly Oshoma et al [ 17 ] in Nigeria found that the median age of children with severe malaria associated to AKI was 3.5 years. Conroy et al [ 6 ] in Uganda found a median age of 3.2 years.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation